Horticulture –Arepository of speciality oils: Horticulture –Arepository of speciality oils - K V LAKSHMI; NATARAJAN SEENIVASAN (Journal of Oilseeds Research, 2023)
There are a number of vegetable oils used in the world by the people in their day to day life for cooking, medicines, fuel...etc of which sunflower oil, safflower oil, sesame oil, palm oil, rape seed oil account for the largest percentage. There are also other oils which are derived from the horticultural crops though used in a small quantity by a small section of people possess an immense value. They are used for a wide range of purposes like medicine, cosmetics, cooking, pesticides, fungicides, perfumes…etc. Different crops produce different kinds of oils used for different purposes. Horticultural crops like fruit crops, vegetable crops, ornamentals, spices, plantations, medicinal and aromatic crops are used for extracting the oils. As the cost of a small amount of these oils is too high, it is a fetching business for the farmers to commercialize the production of these crops.